Direct dating of thick‐ and thin‐skin thrusts in the Peruvian Subandean zone through apatite (U–Th)/He and fission track thermochronometry. (20th March 2013) - Gautheron, Cécile; Espurt, Nicolas; Barbarand, Jocelyn; Roddaz, Martin; Baby, Patrice; Brusset, Stéphane; Tassan‐Got, Laurent; Douville, Eric
Abstract Although the structure of the central Peruvian Subandean zone is well defined, the timing of thrust‐related exhumation and Cenozoic sedimentation remain poorly constrained. In this study, we report new apatite (U–Th)/He (AHe) and fission track (AFT) ages from thrust‐belt and foreland strata along three published balanced cross sections. AHe data from the northern, thick‐skinned domain (i.e. Shira Mountain, Otishi Cordillera and Ucayali Basin) show young AHe ages (ranging from 2.6 ± 0.2 to 13.1 ± 0.8 Ma) compared with AFT ages (ranging from 101 ± 5 to 133 ± 11 Ma). In the southern Camisea Basin, where deformation is mainly thin‐skinned, AHe and AFT ages have been both reset and show young cooling ages (3.7 ± 0.8 Ma and 8 ± 2 Ma respectively). Using low‐temperature thermochronology data and the latest fission track annealing and He diffusion codes, the thermal history of the study area has been reconstructed using inverse modelling. This history includes two steps of erosion: Early Cretaceous and late Neogene, but only Neogene sedimentation and exhumation varies in the different sectors of the study area. From a methodological point of view, large AHe data dispersion point to the need for refinement of AHe damage and annealing models. The influence of grain chemistry on damage annealing, multiple age components and the possibility of fission tracks as traps for He need further consideration. For the central Peruvian Subandes, AHe and AFT ages combined with balanced cross sections emphasize the dominant control of Paleozoic inheritance rather than climate on Cenozoic infilling and exhumation histories. Finally, our data provide the first field example of how thick‐skinned thrust‐related deformation and exhumation in the Subandes can be directly dated through AHe thermochronology.